J-shaped sternotomy in aortic valve repair and ascending aorta replacement. Short-term results - G. A. Akopov; A. S. Ivanov; T. N. Govorova; D. V. Moskalev (Вестник трансплантологии и искусственных органов, 2021)
Objective: to evaluate the short-term outcomes of surgical treatment of aortic valve and ascending aorta defects performed through mini-sternotomy using normothermic cardiopulmonary bypass and hyperkalemic cardioplegia via Calafiori technique from May 8, 2019 to May 14, 2020. Materials and methods. The study enrolled 80 patients with isolated aortic valve disease and combined  pathology of the aortic root and ascending aorta. It lasted from May 8, 2019 to May 14, 2020. The patients were divided into two groups: Group 1 included 30 patients in whom the upper median J-shaped sternotomy was applied as an access, while Group 2 consisted of 50 patients in whom standard median sternotomy was used as an access. The patients consisted of 43 (53.7%) males and 37 (46.3%) females; the average age was 55.1 ± 11.6 years. All patients were examined before surgery. It revealed no statistically significant differences between the two groups. Results. Group 2 had a 30-day mortality of 2% (n = 1) due to the development of acute heart failure against the background of heart rhythm disturbances. One patient in this group had a late mortality due to acute cerebrovascular accident occurring a month after discharge, which corresponded to 2% (n = 1). There were no deaths in Group 1. In Group 1, there were two conversions (6.7%) to longitudinal median sternotomy. In the first case, it was not possible to restore heart rhythm through repeated defibrillator discharges from mini-sternotomy access due to the presence of an adhesive process in the pericardial cavity. In the second case, ligation of the right internal thoracic artery was required after sternal wire sutures. Artificial ventilation (AV)  lasted for 170.9 ± 70.2 minutes in Group 1 and 358.2 ± 169.5 minutes in Group 2. Cardiac activity was independently restored in 23 patients (77%) in Group 1, and in 12 (24%) in Group 2 (p < 0.001). Intraoperative blood loss was 400 ± 150 mL and 850 ± 150 mL (p < 0.05) in Group 1 and Group 2, respectively. In the early postoperative period, it was 200 ± 150 mL in Group 1 and 350 ± 150 mL in Group 2. The length of stay at the intensive care unit and the duration of intensive therapy did not exceed 1 day in both groups. In the early postoperative period, 4 patients in Group 1 (13%) and 27 patients in Group 2 (54%) needed inotropic support (p < 0.001). The need for painkillers and non-steroidal anti-inflammatory drugs was within 3–4 days in Group 1 and 8–10 days in Group 2. In-hospital postoperative period varied from 10 to 16 days in both groups, depending on the severity of the initial condition, presence of concomitant diseases and the need to select an adequate anticoagulant dose. The patients were discharged in satisfactory condition  under the supervision of a cardiologist at their homes. There were no inflammatory complications in the access area in both groups during their in-hospital stay. Among the complications in the mid-term postoperative period, two months after discharge, mediastinitis was observed in Group 2. The patient was re-hospitalized, after a course of antibiotic therapy which resolved the mediastinitis; sternal osteosynthesis was performed. Conclusion. Based on the study, it has been shown that this technique reduces the duration of mechanical ventilation, ensures early extubation, decreases blood loss, and, accordingly, ensures the use of replacement therapy, chest stability and a better cosmetic effect. It should be noted that there was no mortality and sternal complications in the patient group with a minimally invasive approach.